Concepts of Genomics in Kidney Transplantation - Oetting, William S. (Curr Transplant Rep, 2017)
PURPOSE OF REVIEW: Identification of genetic variants to aid in individualized treatment of solid organ allograft recipients would improve graft survival. We will review the current state of knowledge for associations of variants with transplant outcomes. RECENT FINDINGS: Many studies have yet to exhibit robust and reproducible results, however, pharmacogenomic studies focusing on cytochrome P450 (CYP) enzymes, transporters and HLA variants have shown strong associations with outcomes and have relevance towards drugs used in transplant. Genome wide association study data for the immunosuppressant tacrolimus have identified multiple variants in the CYP3A5 gene associated with trough concentrations. Additionally, APOL1 variants had been shown to confer risk to the development of end stage renal disease in African Americans. SUMMARY: The field is rapidly evolving and new technology such as next generation sequencing, along with larger cohorts, will soon be commonly applied in transplantation to understand genetic association with outcomes and personalized medicine.